Answer:
w = 3
General Formulas and Concepts:
Pre-Algebra
- Order of Operations: BPEMDAS
- Equality Properties
Explanation:
Step 1: Define equation
2(w - 1) + 8 = 6(2w - 4)
Step 2: Solve for w
- Distribute: 2w - 2 + 8 = 12w - 24
- Combine like terms: 2w + 6 = 12w - 24
- Subtract 2w on both sides: 6 = 10w - 24
- Add 24 on both sides: 30 = 10w
- Divide 10 on both sides: 3 = w
- Rewrite: w = 3
Step 3: Check
Plug in w into the original equation to verify it is a solution.
- Substitute in w: 2(3 - 1) + 8 = 6(2(3) - 4)
- Multiply: 2(3 - 1) + 8 = 6(6 - 4)
- Subtract: 2(2) + 8 = 6(2)
- Multiply: 4 + 8 = 12
- Add: 12 = 12
Here we see that 12 does indeed equal 12.
∴ w = 3 is a solution of the equation.